Análise de proficiência em modelos de valor adicionado com desempenho passado do aluno: diferencial por tipo de escola pública em Fortaleza-Ce - Holanda, Tiago Lima (2022)
Despite presenting a slower development compared to the initial phases of basic education, secondary education has shown an improvement in proficiency rates in public schools in the State of Ceará, as demonstrated by the Coordination of Evaluation and Monitoring of Education at SEDUC-CE. However, among the different types of schools that exist at this stage of education, there are quite significant variations in student performance results, even within the same Education Network and in a single city. The types of schools that the Secretary of Education of the State of Ceará currently offers in the city of Fortaleza are part-time, full-time and vocational, in addition to two military schools. Besides the difference in methodologies and content for each type, the latter two are distinguished by the performance-based selection processes. That is, they already capture good entry students. Thus, to investigate the school effect by type, it is necessary to control for alumni performance, which happens in value-added models, which is the empirical proposal of this dissertation. Thus, the performance differentials by public school type in Fortaleza are investigated for third year high school students, controlling for their past performance in elementary school (ninth and fifth grades). For this purpose, the SPAECE base was used for several years, where it was possible to concatenate the performance of the same student at different stages. The results showed significant positive differential effects for vocational and military schools, but not for full-time schools.